The genus Muscarella (Orchidaceae): two new synonyms - Thoerle, Lisa (2019)
Recently, the new monospecific genus Vaginaella Vierling (2018: 19) was proposed to accommodate the proposed species Vaginaella stromatolithoides Vierling (2018: 19). After comparing the original description and illustration of Muscarella rojohnii (Luer 2006: 115, 134) and a photograph of the plant from which the holotype was made (Fig. 1) with the description, illustration and photographs in Vierling (2018) and a photograph of the holotype, we conclude that V. stromatolithoides is synonymous with M. rojohnii, and that Vaginaella cannot be separated from Muscarella Luer (2006: 94).